Single cells in confined volumes: microchambers and microdroplets. Issue 3 (13th January 2016) - Hümmer, D.; Kurth, F.; Naredi-Rainer, N.; Dittrich, P. S.
Abstract : Microfluidic devices capable of manipulating and guiding small fluid volumes open new methodical approaches in the fields of biology, pharmacy, and medicine. Abstract : Microfluidic devices capable of manipulating and guiding small fluid volumes open new methodical approaches in the fields of biology, pharmacy, and medicine. They have already proven their extraordinary value for cell analysis. The emergence of microfluidic platforms has paved the way to novel analytical strategies for the positioning, treatment and observation of living cells, for the creation of chemically defined liquid environments, and for tailoring biomechanical or physical conditions in small volumes. In this article, we particularly focus on two complementary approaches: (i) the isolation of cells in small chambers defined by microchannels and integrated valves and (ii) the encapsulation of cells in microdroplets. We review the advantages and limitations of both approaches and discuss their potential for single-cell analysis and related fields. Our intention is also to give a recommendation on which platform is most appropriate for a new question, i.e., a guideline to choose the most suitable platform.